The Influence of Intellectual Capital Dimension on the Performance of Village Apparatus - Deky Hamdani; Fadli Anugrah; Ayu Esteka Sari (International Journal of Economics, Business and Innovation Research, 2024)
This research is entitled The Influence of Intellectual Capital Dimension on the Performance of Village Apparatus. The purpose of this study is to analyze The Influence of Intellectual Capital Dimension on the Performance of Village Apparatus. The sampling technique is by using a full sampling technique with a total of 121 respondents. The type of research used in this study is the survey method, which is a method that aims to collect data with questionnaires. The analysis method used is structural equation modeling (SEM). The conclusion of this study is Human Capital and Organizational capital has a positive effect on Intellectual Capital village apparatus in Pondok City District in Sungai Penuh City. Intellectual Capital and Human Capital has a positive effect on Performance village apparatus in Pondok City District in Sungai Penuh City. But Organizational Capital has no effect on performance village apparatus in Pondok City District in Sungai Penuh City. intellectual capital is a variable that cannot mediate Human Capital and Organizational Capital in the performance of village apparatus.